Fenomena Eksploitasi Tenaga Kerja pada Sektor Food And Beverage Studi Kasus : pada Perusahaan X di Surabaya - Tiyas, Niken Saptaning; Nadia Intan Fadila (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The enactment of the Manpower Law is a government commitment to protecting workers in Indonesia. In the law, labor exploitation is prohibited, as stated in Article 68, Article 74, and Article 81. In reality, labor exploitation, especially in the F&B industry, still occurs, this can be seen in the case that occurred at company X in Surabaya. The purpose of this study is to examine the form such exploitation. This research employs a qualitative descriptive approach, utilizing Karl Marx conflict theory for analysis and reviewing the issue from a legal perspective based on Law Number 13 of 2003 Concerning Manpower. The Study adopts a case study format, with data collected thriugh observation, interviews, and documentation techniques. The results of the study indicate that the form of labor exploitation that occurs at company X is carried out in the form of employing workers outside the specified working hours, not paying basic wages and overtime wages, imposing harsh treatment on workers, and withholding diplomas and ID cards belonging to workers, all of which violate the Manpower Law. The impacts caused by labor exploitation in company X include psychological stress, trauma, and fear of re-exploitation by the company.